The T7-Primer Is a Source of Experimental Bias and Introduces Variability between Microarray Platforms - Kerkhoven, Ron M.; Sie, Daoud; Nieuwland, Marja; Heimerikx, Mike; De Ronde, Jorma; Brugman, Wim; Velds, Arno (PloS one, 2008)
Eberwine(-like) amplification of mRNA adds distinct 6-10 bp nucleotide stretches to the 5' end of amplified RNA transcripts. Analysis of over six thousand microarrays reveals that probes containing motifs complementary to these stretches are associated with aberrantly high signals up to a hundred fold the signal observed in unaffected probes. This is not observed when total RNA is used as target source. Different T7 primer sequences are used in different laboratories and platforms and consequently different T7 primer bias is observed in different datasets. This will hamper efforts to compare data sets across platforms.